Predicting the fire performance of LSF walls made of web stiffened channel sections. (1st August 2018) - Dias, Yomal; Keerthan, Poologanathan; Mahendran, Mahen
Highlights: Developed a new web-stiffened channel stud for LSF wall applications. The new stud section has greater structural efficiency and economy. Developed extended Fire Resistance Level versus Load Ratio curves. Effect of stud geometry on the fire performance of LSF walls is minimal. Structural failure of non-load bearing walls in fire is possible. Abstract: Fire performance of plasterboard lined Light-gauge Steel Framed (LSF) walls has been investigated using numerical and experimental studies in the past. However, past research has been limited to lipped channel sections (LCS) and welded hollow flange channel (HFC) sections. This paper investigates the fire performance of LSF walls made of a new web-Stiffened Channel Section (SCS) stud using numerical models, validated using available fire test results. The SCS succeeds in eliminating both local and distortional buckling when used as 3 m long LSF wall studs at ambient temperature. Ambient temperature compression capacity evaluations showed that the performance of the SCS is equivalent to the welded HFC, but is superior to the LCS. Fire performance of load bearing and non-load bearing LSF walls made with each of the three stud sections was assessed for three common wall configurations using thermal and structural finite element analyses. Extended FRL versus Load Ratio curves were developed using a combination of steady state and transient state coupled temperature-displacement analyses. The results showed that the effect of stud geometry on the fire performance of LSF wall configurations is minimal. Under the same load ratio, all three stud sections perform similarly in each of the wall configurations. Considering the ambient and fire performance results, the reduced cost and also the potential double connectivity to plasterboard via its lip elements, the SCS is recommended for use in LSF walls. This paper has also highlighted the susceptibility of non-load bearing LSF walls to fail in fire under structural inadequacy.